Vegetative Growth Analysis of Mustard Greens (Brassica juncea L) Consequences of Vermicompost and Urea Fertilizer Treatment - Raksun, Ahmad; Ilhamdi, Liwa; Merta, I Wayan; Mertha, I Gde (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Research on Analysis of vegetative growth of mustard greens (Brassica juncea L) due to vermicompost and urea fertilizer treatment was carried out from April to July 2024 In West Lombok. This research aims to analyze: 1) vegetative growth of green mustard after urea fertilizer treatment, 2) vegetative growth of mustard greens after vermicompost treatment 3) the interaction effect of vermicompost and urea fertilizer treatment on the growth of green mustard. In the research a 2 factor design was used. Growth parameters of mustard greens measured were plant fresh weight, stem height, number of leaves and length of mustard green leaves. Data from measurements of all the growth parameters above were analyzed using analysis of variance. The results of the mustard green growth analysis showed that: (1) urea fertilizer treatment had a significant effect on fresh weight, plant height, number of leaves and leaf length of mustard greens, (2) vermicompost treatment had a significant effect on all mustard green growth parameters. (3) the interaction between urea and vermicompost fertilizer treatments did not have a real effect on the growth of mustard greens.